Explore Westonci.ca, the premier Q&A site that helps you find precise answers to your questions, no matter the topic. Explore a wealth of knowledge from professionals across different disciplines on our comprehensive platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.

Review the proof of the identity cos(π − A) = −cosA.

cos(π − A)

Step 1: = cosπcosA − sinAsinπ

Step 2: = (−1)(cosA) + (sinA)(0)

Step 3: = −1cosA + (sinA)(0)

Step 4: = −cosA + 0

Step 5: = −cosA

At which step was an error made?

step 1
step 2
step 3
step 4